Development and validation of a nitrogen dioxide passive sampler - Elahe Hasannezhad Estiri; Abolfazl Rahmani Sani; Afshin Dowlatabadi; Reza Hasannezhad Estiri; Mohammad Miri (MethodsX, 2023)
Nitrogen dioxide (NO2) is one of the main indicators of traffic-related air pollution in urban areas. Active sampling methods (common methods) are expensive and need advanced devices. While Passive sampling is a simple and low-cost method for measuring air pollutants, including NO2. Therefore in this study, we developed a passive sampler to measure ambient NO2 and validation its performance by comparing it with active sampling methods. Ambient NO2 was measured for 24 h by both active and passive sampling methods in the same locations (2 m height above grand level and 15 m distance from air pollution sources). Sampling of NO2 was repeated for 18 days to compare ambient NO2 concentrations measured by active and passive methods and validation our developed passive samplers. • To develop passive samplers we used three stainless steel filters impregnated with a combination of triethanolamine and acetone (25:25 mL) in each tube. • Active NO2 sampling was conducted using the modified Satlzman method (standard method). • There was a strong correlation between NO2 concentration obtained from active and passive sampling methods (r = 0.84).